Peran Media Sosial Dalam Pencegahan Kanker Payudara: Literatur Review - Tasya Alviyatun Nikmah; Meilia Rahmawati Kusumaningsih (Universitas Islam Jember, 2025)
Breast cancer is one of the most common types of cancer in several countries, with its disease burden projected to increase, particularly in nations with weak healthcare systems. In Indonesia, breast cancer is among the leading causes of cancer-related mortality. The number of breast cancer cases in Indonesia is estimated to increase by up to 63% between 2025 and 2040. One of the contributing factors to breast cancer is delayed awareness of the disease, along with limited knowledge regarding its symptoms and appropriate methods of examination. Several studies have demonstrated that social media plays an important role in breast cancer prevention. This literature review aims to analyze and synthesize the findings of previous studies related to this topic. The literature was obtained through searches of the Google Scholar and PubMed databases, focusing on publications from 2019 to 2025. This review includes articles indexed in Sinta and Scopus. The analysis of both international and national studies indicates that social media has a significant role in breast cancer prevention, functioning as a source of information, a platform for health campaigns, a promotional medium, and a tool for health education.